Scattered Slum Islands: Insurgent Citizenship Phenomenon Related to The Provision of Public Services in Wedi Kengser Settlement, Yogyakarta - Febrianto Wibowo; Kurniawati Dewi Arifah; Putu Ananda Sanjiwani Saskita; Rizka Lintang Peksiwari; Yulia Pratiwi (Kementerian Perencanaan Pembangunan Nasional (Bappenas), 2018)
United Nation Habitat (UN-Habitat) predicts that in 2050, 66% of the world community will live in the city. There is a group of disadvantaged communities, who is called a community of urban poor, such as Wedi Kengser settlement in the community of Kampung Ledhok, and the community of Kampung Gondolayu Lor, Yogyakarta. The government sees them as people who live illegally, as a result of the illegal land placement. They can’t get basic public services. The implication is that their rights aren’t fulfilled, to obtain social services and poverty alleviation from local governments. Thus, they collectively make a habitable shelter by creating a series of programs such as society at large and by maintaining their values. This phenomenon of society to obtain their rights is identified as an